Effectiveness of an Innovative Pulsed Electromagnetic Fields Stimulation in Healing of Untreatable Skin Ulcers in the Frail Elderly: Two Case Reports. (8th November 2015) - Guerriero, Fabio; Botarelli, Emanuele; Mele, Gianni; Polo, Lorenzo; Zoncu, Daniele; Renati, Paolo; Sgarlata, Carmelo; Rollone, Marco; Ricevuti, Giovannoi; Maurizi, Niccolò; Francis, Matthew; Rondanelli, Mariangela; et al.
Abstract : Introduction . Recalcitrant skin ulcers are a major burden in elderly patients. Specifically, chronic wounds result in significant morbidity and mortality and have a profound economic impact. Pulsed electromagnetic fields (PEMFs) have proved to be a promising therapy for wound healing. Here we describe the first reported case of an innovative PEMF therapy, Emysimmetric Bilateral Stimulation (EBS), used to successfully treat refractory skin ulcers in two elderly and fragile patients. Case Presentation . Two elderly patients developed multiple chronic skin ulcerations. Despite appropriate treatment, the ulcers showed little improvement and the risk of amputation was high. Both patients underwent daily EBS therapy and standard dressing. After few weeks of treatment, major improvements were observed and all ulcers had healed. Conclusion . In patients with refractory ulceration, EBS therapy may be of real benefit in terms of faster healing. This case supports the supportive role for PEMFs in the treatment of skin ulceration in diabetes and is suggestive of a potential benefit of EBS in this clinical condition.